Optimasi Penugasan Mekanik Menggunakan Metode Penugasan di Deta Yamaha Singaparna Tasikmalaya - Wahyu Teri Aripin; Mamik M. Fuadi; Dede Hendarwan (LPPM Sekolah Tinggi Teknologi Cipasung, 2022)
Deta Yamaha Singaparna is one of the companies engaged in motorcycle sales and Yamaha motorcycle services. The object of the research is the assignment of service mechanics related to the optimization of mechanical assignments at Deta Yamaha Singaparna. This research is a quantitative research using the Assignment Method. The data was processed from the results of time measurements by four mechanics when working on servicing four types of motors, namely Matic Injection, Sport Injection, Carburetor Underbone, and Injection Underbone. The analysis was carried out using the Assignment Method. Based on the results of the analysis, Arman's mechanic works on the Sport Injection (SI) type of motorcycle, Edward's mechanic works on the Karbu Underbone (BK) motorcycle, and the human mechanic works on the Underbone Injection (BK) motorcycle type, and Lutfi's mechanic works on the Matic Injection (MI) motorcycle type. The total time using the Assignment Method was 146 minutes, while the previous total time was 174 minutes. There was a time saving of 28 minutes. The second solution is obtained so that the mechanical assignment can be optimal. Deta Yamaha Singaparna can change the assignment of mechanics so that service activities can run optimally so that mechanics get assignments based on optimal time results when working on Yamaha motorcycle services.